Systematic investigation of Pimpinella saxifraga in Germany - Jawarneh, Mohammad Saleh Mahmoud; Justus Liebig University Giessen (My University, 2022)
Introduction: This study focuses on Pimpinella saxifraga L. (Apiaceae), native in Germany. Pimpinella contains about 180 species all over the world being one of the largest genera in the Apiaceae. Due to large morphological variation and the wide range of geographical distribution, it is taxonomically complex. We hypothesize, that 1) molecular data can separate individuals from biogeographic regions in Germany; 2) that morphological features discriminate taxa from Germany; 3) molecular and morphological data will be congruent in their information content about diversity of P. saxifraga in Germany. Material and methods: We investigated 78 individuals from different German herbaria by morphology and genetics. 44 SSR Nuclear microsatellite markers evolved for different Apiaceae taxa were estimated for inter-generic transferability to P. saxifraga. We investigated five quantitative and six qualitative morphological traits to compare individuals from biogeographical regions and different altitudes. Result: The transferability of nine nuclear microsatellite markers from D. carota to P. saxifraga were successful. A total of 122 alleles were gained with a mean of 12.4 alleles per marker. The level of expected and observed heterozygosity per markers extended from 0.31 to 0.95 and 0.27 to 0.82 respectively in 9 primers The average polymorphic information content values ranged from 0.25 to 0.85 with an average of 0.57. High genetic diversity (He = 0.61) within and among P. saxifraga individuals were detected. Mantel tests detected significant correlation between genetic and geographical distance. Analysis of molecular variance (AMOVA) specified that the molecular variance existed within regions (98%) rather than among regions (2%). STRUCTURE analysis presented two genetic clusters (K=2) described the SSR data supported by factorial analysis and principal coordinate analysis (PCoA). Hierarchical neighbor-joining tree (NJ) showed also low level of genetic differentiation between 78 individuals according to biogeographical regions. Factorial analysis and STRUCTURE analysis using leaflet morphological character states detected two major clusters. Cluster I with pinnatifid lobed linear teeth; cluster II with ovate serrate teeth, confirmed by unweighted Neighbor-Joining tree (NJ) and Median-joining network. No match of leaf morphological differences with geographical distances was found. Conclusion: This is study is the first of the genetic population structure and genetic diversity of German P. saxifraga using nine SSR markers. The correlation of the individuals with their geographical regions was very low. Neither genetic markers nor morphological traits revealed any connection to the geographic region but separate taxa as groups. Morphological characters of P. saxifraga provide a key for taxa identification but do not explain their taxonomic status as species. The applicability of our results to the formerly published morphological records is limited, mainly due to ambiguous terminology. More work is needed to define the effect of cultivation on qualitative vegetative and reproductive traits of P. saxifraga taxa, in addition to the application of further specific molecular markers.
Keywords: Pimpinella saxifraga; SSR microsatellites; Population genetic structure; ddc:580